Excluding site specific data from the LCA inventory. - Ross, Stuart
The exclusion of site specific data from the inventory phase of an LCA continues to be a point of controversy. Though the current simplified data collection strategy is widely supported by the LCA community, there are still many who are concerned about the implications this limitation has for the utility and reliability of LCA results. This is particularly relevant to practitioners who are attempting to draw conclusions about the environmental performance of different systems for the development of environmental policy. The current site generic methodology introduces uncertainties into LCA results that have the potential to misdirect decisions on improvement measures. Therefore, in this paper we assess the practicality of collecting site specific data and examine its value for study interpretation and decision making. In our case study, we compare the contribution of a number of plastics based packaging systems to photochemical oxidant formation. Our results demonstrate that the aggregation of photochemical oxidant precursor emissions into a single global parameter is an unreliable indicator of environmental burden and that the real significance of each packaging's contribution to the formation of photochemical smog in the atmosphere can only be understood after the addition of spatial and temporal information. We conclude that for non-global cumulative impact categories, additional spatial and temporal data should be collected and that the benefits to decision makers far outweigh the additional effort needed to acquire this data for the LCA inventory.
Keywords: Data aggregation; ISO standards; Life cycle assessment; Photochemical oxidants; Plastic packaging; Recycling; Re-use.; Site specific data